Magnesium Sulfate in Exacerbations of COPD in Patients Admitted to Internal Medicine Ward - Solooki, Mehrdad (Iran J Pharm Res, 2014)
The purpose of this study was to examine the effect of intravenous magnesium sulfate on patients with COPD exacerbation requiring hospitalization. In this randomized clinical trial 30 patients with COPD exacerbation were studied. Patients were randomly assigned to group A (case) who concurrent with standard therapy received 2 g magnesium sulfate in normal saline infused in 20 minutes on days one to three and group B (control) who received standard medications and placebo. PEFR and FEV1 were measured by before, 45 minutes and third day of entering the study. Vital signs HR, BP, RR, temperature and SpO2 were monitored during hospitalization. 21 males and 9 females patients with mean age of 68 ± 9 years, case 67 ± 10 and control 70 ± 8 were studied (15 patients in each arm of study). The mean pretreatment FEV1 was 26% ± 12, and 35% ± 18 in case and control groups respectively (P=0.137). FEV1 after 45 minutes in case group was 27% ± 9 and control group 36% ± 20 (p=0.122). FEV1 after 3 days of study was 32% ± 17 in case and 41% ± 22 in control groups (P=0.205). The mean pretreatment PEFR was 126 ± 76 l/min in case and 142 ± 62 l/min in control groups (P=0.46). Changes in PEFR were not significant 45 min (p=0.540) and 3 days (p=0.733) of the administration of intravenous magnesium sulfate. Duration of hospital stay between the two groups did not show any significant difference. This study showed that administration of intravenous magnesium sulfate in hospitalized patients with COPD exacerbation neither revealed any significant bronchodilating effect nor reduced duration of hospital stay.